La problemática operativa en la factura electrónica como elemento de deducción - Cortés Benítez, Angélica (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The following investigation provides knowledge regarding the process of electronic billing as a means for proof as required by the norms of the income tax. This is addressed to every kind of contributor; be they micro, small, medium, or large business, it’s also aimed at physical persons and/or moral persons that have the obligation of issuing fiscal receipts. ELECTRONIC BILL: It’s a digital or electronic document that integrates the information pertinent to the fiscal receipt, with security elements, that has the certification of the contributor and the SAT. The Federal Fiscal Code in its 27th article dictates that “the moral persons as well as the physical ones that have to present periodic declarations or are obligated to issue fiscal receipts for the acts or activities that they perform, or by the income they perceive…” REQUIREMENTS TO ISSUE ELECTRONIC RECEIPTS • possess the advanced electronic signature (FIEL) or, in some cases, use the password. • Have the digital seal certificate. Physical persons can use their FIEL certificate. • Utilize the SAT’s free tool. • Seek a receipt assistant. • Use the fiscal registry system.

El presente trabajo da a conocer el proceso de la factura electrónica como medio de comprobación para efectos del Impuesto Sobre la Renta. Va dirigido a todo tipo de contribuyente, ya sean micro, pequeñas, medianas y grandes empresas asimismo para personas físicas y7o morales que tengan la obligación de emitir comprobantes fiscales. FACTURA ELECTRONICA: Es un documento digital o electrónico que integra los datos de comprobante fiscal, con elementos de seguridad, que cuenta con la certificación del contribuyente y del SAT. El código fiscal federal en su artículo 27 nos señala que “las personas morales así como las físicas que deban presentar declaraciones periódicas o que estén obligadas a expedir comprobantes fiscales por los actos o actividades que realicen o por los ingresos que perciban…” REQUISITOS PARA EXPEDIR FACTURAS ELECTRONICAS: • Tener firma electrónica avanzada (FIEL) o en algunos casos, utilizar la contraseña • Contar con el certificado de sello digital. Las personas físicas podrán utilizar su certificado de la FIEL • Utilizar la herramienta gratuita del SAT • Acudir con un auxiliar de facturación • Utilizar el sistema de registro fiscal.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Fiscal
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2014-1829; Contribuyente; CFDI; Internet; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6049